2015
DOI: 10.1556/2006.4.2015.044
|View full text |Cite
|
Sign up to set email alerts
|

Risk for exercise dependence, eating disorder pathology, alcohol use disorder and addictive behaviors among clients of fitness centers

Abstract: Background and AimsExercise dependence (EXD) is considered a behavioral addiction that is often associated with eating disorders. To date, only few studies examined the potential overlap between EXD and other addictive behaviors. Therefore, the present study aimed at investigating the relationship of EXD with pathological buying, pathological video gaming (offline and online), hypersexual behavior, and alcohol use disorder in a sample of clients of fitness centers.MethodsThe following questionnaires were answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 43 publications
4
64
1
1
Order By: Relevance
“…If exercise addiction, by definition, is linked to an escape from stress (Egorov & Szabo, 2013) and has to result in some negative outcome to be considered morbidity (Szabo, 2010), then high scores of exercise addiction in passionate and dedicated athletes may represent a “false alarm” in assessment. Indeed, in accord with the new conjecture (Szabo et al., 2015) that the interpretation of the items aimed at gauging exercise addiction may vary among individuals, especially athletes, our results show that passion and dedication may be two of the many possible moderators that may also include social physique anxiety (Cook et al., 2015), eating disorders (Müller, Loeber, Söchtig, Te Wildt, & De Zwaan, 2015), and/or trait anxiety and depression (Weinstein, Maayan, & Weinstein, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…If exercise addiction, by definition, is linked to an escape from stress (Egorov & Szabo, 2013) and has to result in some negative outcome to be considered morbidity (Szabo, 2010), then high scores of exercise addiction in passionate and dedicated athletes may represent a “false alarm” in assessment. Indeed, in accord with the new conjecture (Szabo et al., 2015) that the interpretation of the items aimed at gauging exercise addiction may vary among individuals, especially athletes, our results show that passion and dedication may be two of the many possible moderators that may also include social physique anxiety (Cook et al., 2015), eating disorders (Müller, Loeber, Söchtig, Te Wildt, & De Zwaan, 2015), and/or trait anxiety and depression (Weinstein, Maayan, & Weinstein, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the higher prevalence of ED in athletes, some athletes, especially endurance athletes, comprise a group which is furthermore at higher risk for harmful excessive exercise, the so-called exercise dependence (EXD) [21]. Prevalence for EXD is 0.5-3.5% in the general population [22] and up to > 50% within triathletes [23]. Some research groups also describe pathological excessive exercise as 'exercise addiction' [24][25][26][27][28][29][30][31][32].…”
Section: Exercise Dependence In Athletesmentioning
confidence: 99%
“…There is also evidence that this behavior is carried out, at least to some extent, in fitness centers. Estimates of between 8% [23] and 43% [24] of "exercise dependence prevalence" have been reported, with Stapleton and colleagues [25] reporting at least a single occurrence in 43% of their male gym-using sample.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that prevalence of eating disorders among such exercisers is higher than among competitive and organized sports participants [26]. Muller and colleagues reported that 10.9% of their sample of fitness center clients fulfilled the criteria for an eating disorder, as assessed by the Eating Disorders Examination-Questionnaire [23]. Stapleton and colleagues [25] reported at least one occurrence of binge eating or dietary restraint in 35 and 15%, respectively, of male fitness center clients.…”
Section: Introductionmentioning
confidence: 99%